Spatial misallocation and economic development - Li, Xiaolu (2017)
This thesis contains three chapters with a focus on how frictions at institutional or firm-level affect the resource allocation, market performance and welfare outcome. I quantitatively examine the aggregate implications and distributional impacts of those frictions both at the aggregate and at the city-level. Chapter 1 provides the motivation of the thesis, highlights the major contribution of each chapter to the literature, together with a summary of the main results in each chapter. Chapter 2 focuses on a unique institutional feature of China. Local government has great control over land supply in each city. Local officials decide the quantity of land to sell on the market, and can also use land as collateral to obtain funds from state-owned banks to finance local expenditures. The main motivation for this is to promote GDP growth, which is a key performance indicator for the promotion of local officials. What are the implications on GDP and welfare of this unique institutional design? In this chapter, I develop a competitive spatial equilibrium framework to study these issues. In the model, each local government attempts to maximize local GDP by deciding how much residential land to supply to the market. Local government finances its expenditure both by land sales revenue and by borrowing from state-owned banks using land as collateral. Individual workers optimally choose locations and will migrate to other cities if housing prices in their home cities are too high. I calibrate the model to the Chinese economy in 2010. I compare the benchmark equilibrium outcome with a first-best allocation. I also examine the role of local GDP tournaments, by studying a counter-factual situation where the objective of local government is to maximize the utility of local individual’s. The results suggest that in the first-best allocation the largest city will be larger and the smaller cities smaller. The welfare level achieved in our benchmark economy is not significantly lower than in the other two scenarios. Chapter 3 develops a general equilibrium framework with heterogeneous firms to quantitatively evaluate the welfare implications of firm-level frictions at both the aggregate and city level in China. I use individual firm data to estimate output and labor frictions for each city and for state-owned and private firms. Our results show that state-owned firms usually have lower labor frictions and higher output frictions, although the gaps have been shrinking over time. The existing frictions had distorted employment toward SOEs. The frictions had worsened over time, leading to approximately 11 percent welfare loss between 2000 and 2005. Chapter 4 is a study on Singapore housing market. Numerous countries in the world provide their citizens and residents cheap public housing, whereas foreigners are only allowed to purchase relatively scarce and expensive private housing. Undoubtedly, the growth in native (foreign) population size will directly contribute to a higher public (private) housing price, and indirectly induce a higher private (public) housing price via general equilibrium effects. The question is how to quantitatively evaluate the magnitude of each impact. To address this issue, I propose a dynamic general equilibrium framework with heterogenous native and foreign agents interacting in both public and private housing markets. Natives can upgrade from public to private housing over their life-cycle. I also allow the option that foreigners choose to convert to a permanent residentship, then compete with natives in the public housing market. I calibrate the model into Singapore economy from 1991-2015. The calibrated model can account for about 64.9 percent of private housing price growth, and account for 61.7 percent of public housing price growth in the data. The decomposition exercises suggest that the growth of native population can generate about 76.1 percent of private housing price growth, while the growth of foreign population can generate about 78.7 percent of public housing price growth. Finally, the relaxation of borrowing constraint can generate a substantial rise in private housing price.